Da concepção e funções da universidade ao plano de desenvolvimento institucional (PDI): estudo de caso da Universidade do Sul de Santa Catarina - Schmitz Neto, Valter Alves (2011)
In this research, it seeks to understand the concept of university, from a case study of Unisul, in its search to make an important social role in the process of the regional development. To this end, it analyzed the conception and functions of Unisul, while university, in the materiality expressed in the Institutional Development Plan (IDP). To achieve this goal, it identified the university project proposed, strategies, planning, institutional management, the process of institutional development, the regional integration, and especially the functions assumed by the higher education. In the perspective of the document analysis, it was made a comparative study between IDP 2005/2009 and IDP 2010/2014. The theoretical studies allowed the tension between the dimensions of IDP, the alignment in relation to the conception and function of the university, its political organization, teaching, management, and its role with the demands of the society. The identification of the project of university, based on the concepts of education and university, the principles of knowledge production, policies and guidelines for education expressed in the laws of national education to higher education and the university, were necessary to purposes of this study. They also were discussed: the principles of democracy and the university management that characterized IDP and its impacts on the development regional in the attendance of the expectations and demands of society. For this, it was a qualitative study of documentary character, which contributes to studies, especially about the conception, functions, political organization, and management-oriented teaching the principles of strategic planning expressed in the IDP. In summary, our results allowed us to identify elements to understand the linkage among categories analysis, comparing the different planning cycles expressed in IDPs: the university development, knowledge production, planning and management, and regional development, which underlie the Project designed by the UNISUL University